DDT : Scientists, Citizens, and Public Policy - Dunlap, Thomas R., 1943- (Book collections on Project MUSE., 2014)
From the time the public learned of DDT's dramatic containment of a typhus epidemic in Naples during World War II to the ban on DDT by the Environmental Protection Agency in 1972, this is the story of the controversial pesticide and its part in the rise of the environmental movement. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important bo.